THU0356 Is there an Association between Skin and Joint Involvement in Patients with Psoriatic Arthritis Treated with Adalimumab? – Data-Analysis From a Large German Non-Interventional Study. (23rd January 2014) - Behrens, F.; Koehm, M.; Thaci, D.; Krummel-Lorenz, B.; Greger, G.; Wittig, B.; Burkhardt, H.
Abstract : Background: In Psoriatic Arthritis (PsA) skin and joint manifestations usually occur in parallel. To explore the association between both, severity of skin disease, joint involvement as well as characteristics of joint and skin manifestations were analysed. Methods: To evaluate data from a multicenter, non-interventional study of PsA patients (n= 1918) treated at different dermatology and rheumatology centers in Germany, descriptive statistics and stepwise regression analyses were used. Patient's data were analysed empirically grouped by baseline target lesion score (TLS) into patients with mild (low TLS, ≤ 3), moderate (intermediate TLS, 4 to 10), or severe (high TLS, 11 to 15) skin disease. Results: Stepwise regression analyses demonstrated no significant association between skin severity and joint manifestations at baseline or after 12 months of adalimumab (ADA) treatment. At baseline, the subgroup with high baseline TLS scores (severe skin disease) had an increased proportion of patients with moderate to severe nail psoriasis (61.6% vs 16.6% for low baseline TLS)), dactylitis (43.9% vs 29.0% for low baseline TLS), and enthesitis (24.6% vs 14.3% for low baseline TLS). The TLS at baseline was significantly correlated with nail psoriasis, the physician global assessment of overall disease activity, and concomitant treatment with methotrexate (MTX) (r < 0.0001). All three TLS subgroups showed improvements in skin and joint manifestations during ADA therapy. The reduction of TLS exceeded in patients with high baseline TLS (severe skin disease) or in those who had received concomitant treatment with MTX. High body mass index (BMI) was significantly associated with a lack of improvement in cutaneous manifestations during therapy. Conclusions: The severity of skin manifestations is not associated with the severity of peripheral joint disease in patients with PsA. Patients with mild skin disease may have extensive musculoskeletal involvement and vice versa. ADA is effective in PsA treatment regardless of baseline skin severity. Disclosure of Interest: F. Behrens Grant/research support from: Abbott, Consultant for: Abbott, M. Koehm Grant/research support from: Abbott, D. Thaci Grant/research support from: Abbott, Consultant for: Abbott, B. Krummel-Lorenz Grant/research support from: Abbott, Consultant for: Abbott, G. Greger Employee of: Abbott, B. Wittig Employee of: Abbott, H. Burkhardt Grant/research support from: Abbott, Consultant for: Abbott